SafeSecRETS: A Safety and Security Requirements Tool for Critical IoT Systems - Veiga, Ernesto Fonseca; Kudo, Taciana Novo; Bulcão-Neto, Renato de Freitas (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de Software, 2025)
[Context] Assuring safety and security from the earliest stages of development is essential, particularly for critical systems. However, addressing these requirements in complex and heterogeneous systems such as those based on the Internet of Things (IoT) is challenging. These systems often operate in dynamic and diverse environments, where vulnerabilities can lead to severe consequences if not effectively mitigated. [Objective] This paper presents SafeSecRETS, a tool supporting safety and security Requirements Engineering (RE) for critical IoT systems. [Method] The tool features a collaborative pipeline with a strategic canvas-based IoT project planning and an extended Systems-Theoretic Process Analysis (STPA) method for safety and security. [Results] SafeSecRETS assists requirements engineers, domain experts, and other stakeholders in collaboratively defining project scope and eliciting, analyzing, and specifying system requirements. Its interconnected visual components guide users through this process, fostering engagement among information, people, and decision-making. A case study on an automated insulin delivery system illustrates the tool’s applicability and presents its structured and integrated approach to RE safer and more secure critical IoT systems. SafeSecRETS demo video:  https://zenodo.org/records/17000378